Development programme motor function of children with mental retardation - Kozina, Zh.L.; Borisiuk, M.V.; Bazilyuk, T.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to study the rehabilitation program recovery of motor function of children with mental retardation. Material-methods: the study involved 19 students from primary diagnosis - mental retardation. Age of children was 8 - 9 years and 9 - 10 years. Motor speed detection reaction carried out using a falling line setting (in cm.) Determination of speed integral motor actions performed with running 30 meters to go. From cross-country test also used the shuttle run 4x9 meters. Results : a program of exercise for children with mental retardation. Exercises aimed at correcting the basic movements, flexibility correction, correction and development of coordination abilities, adjustment and development of physical fitness, correction and prevention of secondary fractures. Conclusions : it was found that the rehabilitation program for development and correction of motor function of children with mental retardation is an effective and affordable to adjust coordination abilities and flexibility.